2001
DOI: 10.1046/j.1365-8711.2001.04717.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad emission lines from the opaque electron-scattering environment of SN 1998S

Abstract: A B S T R A C TI propose that broad narrow-topped emission lines with full width at zero intensity .20 000 km s 21 revealed by early-time spectra of SN 1998S originate from a dense circumstellar shell (CS) with an outer radius R < 10 15 cm. The tremendous line width is the result of multiple scattering of the photons of the narrow line by the thermal electrons of the opaque CS gas. The Ha line on 1998 March 6 is reproduced by Monte Carlo simulations, provided that the Thomson optical depth of the CS shell is 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…6. We note the remarkable resemblance of this proposed CSM configuration to the density profile calculated by ref 29. (Fig.…”
supporting
confidence: 79%
“…6. We note the remarkable resemblance of this proposed CSM configuration to the density profile calculated by ref 29. (Fig.…”
supporting
confidence: 79%
“…This profile may be also interpreted as a narrow core with broad wings resulting from multiple scattering events with thermal electrons, an escape mechanism for line photons favoured by the small photospheric velocity observed for SN 2008S at all phases (Dessart et al 2009). The electron scattering in a dense (Thomson optical depth of ∼3–4) CS shell lying beyond the SN photosphere was suggested by Chugai (2001) as an explanation for the very broad wings of Hα in SN 1998S. We compare the Hα profiles of SN 1998S and SN 2008S in Fig.…”
Section: Spectroscopic Data Reduction and Analysismentioning
confidence: 90%
“…The high density of the CS shell in the case of SN 1998S implies that a CDS forms at the interface of SN ejecta and the CSM. The absence of broad P‐Cygni profiles was explained with obscuration by the CDS (Chugai 2001). Fassia et al (2001) showed that absorption troughs appeared in the spectra of SN 1998S after only 12 d, and suggested that the SN ejecta had over‐run the inner CS by that point.…”
Section: The Nature Of Sn 2008smentioning
confidence: 99%
See 1 more Smart Citation
“…Dust formation in the ejecta can be ruled out for the early epochs (26- Alternatively, the photosphere is in front of the forward shock and the emission line velocities do not represent physical motion of the shock but are rather caused by Thompson electron scattering (13,40,52). As the photosphere recedes it will be located behind the forward shock Figure 4).…”
Section: Our High-resolution Data Set Clearly Shows That the Intermedmentioning
confidence: 99%